(untitled) (Psychology Travelogs, 2025)
Tense interpersonal interactions, marked by emotional intensity and communicative strain, present a unique challenge in both personal and professional contexts. This article investigates the role of emotional intelligence in shaping and managing such interactions through the lens of five key preconditions. The study explores how emotionally intelligent individuals interpret verbal and non-verbal cues, regulate emotional responses, and adapt their communicative behaviour in real time. Particular attention is given to how emotional intelligence supports empathy, emotional regulation, and sensitivity to social dynamics, thereby preventing escalation and fostering constructive dialogue. The article emphasises that emotionally attuned communication not only defuses tension but also deepens mutual understanding, transforming conflict-prone exchanges into opportunities for relational growth and collaboration.